A dictionary of construction, surveying, and civil engineering / Christopher A Gorse; David Johnston; Martin Pritchard, (Civil engineer) - Gorse, Christopher A.
An A to Z of construction, surveying, and civil engineering terms covering all core aspects, this book provides a one-stop reference for construction students and professionals.